Clonal hematopoiesis in patients with cancer and its association with risk of thrombosis and prognosis of disease - Cornelia Englisch; Roland Jäger; Jasmina Gassner; Alice Assinger; Matthias Preusser; Peter Valent; Ingrid Pabinger; Cihan Ay (Research and Practice in Thrombosis and Haemostasis)
Background: Patients with cancer are at high risk for cardiovascular events, especially venous and arterial thromboembolism (VTE/ATE). Clonal hematopoiesis (CH) has been identified as risk factor for cardiovascular diseases. However, there is limited insight into the impact of CH on thrombosis risk in patients with cancer. Objectives: The aim of this study was to elucidate the association between CH and cancer-associated VTE and ATE within the framework of the Vienna Cancer and Thrombosis Study (CATS), a prospective observational cohort study. Methods: Peripheral blood DNA samples collected at study inclusion were screened for CH-associated mutations. Results: In this study, 967 patients (median age: 61 [interquartile range, IQR: 50-68] years, 49.9% female) were included and followed-up for a median of 24 (IQR: 24-24) months. Of those, 787 (78.3%) had newly diagnosed cancer and 434 (44.9%) had stage IV disease. We identified 52 CH-associated variants in 46 patients (4.8%). Mutations in the genes DNMT3A (48.1%) and TP53 (17.3%) were most commonly found. The presence of CH was not associated with VTE (adjusted subdistribution hazard ratio: 0.68, 95% CI: 0.21-2.19) or ATE risk (adjusted subdistribution hazard ratio: 1.08, 95% CI: 0.15-8.06). Available laboratory parameters and inflammatory and hemostatic biomarkers did not differ according to CH carrier status. Compared with patients without CH, those with CH showed decreased overall survival; however, this was not independent of age. Conclusion: In our cohort of patients with cancer, the presence of CH was not associated with an increased risk of VTE or ATE. CH had no independent impact on overall survival.